2019
DOI: 10.33086/mtphj.v3i2.1206
|View full text |Cite
|
Sign up to set email alerts
|

Hubungan Leukosit Dan Protein Urine Pada Ibu Hamil Trimester Iii Di Puskesmas Klampis Bangkalan Madura

Abstract: Most pregnant women give birth normally, but 15% of cases are life-threatening complications including preeclampsia. Preeclampsia is marked by an increase in proteinuria, whereas protein is closely related to leukocytes because the breakdown of proteins into amino acids is carried out by enzymes present in leukocytes, especially neutrophil cells. This study aims to determine the relationship between urine leukocyte levels and protein in urine in third trimester pregnant women. The research design used was anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
1
0
7

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 0 publications
0
1
0
7
Order By: Relevance
“…The results of this study were correlated with previous research conducted by Andreas in 2019, where there was no relationship between leukocytes and urine protein in third-trimester pregnant women. 13 This could be due to the failure to divide the severity of COVID-19. Previous studies showed that proteinuria in moderate, severe, and critical COVID-19 was 4.7%, 27.6%, and 63.2%, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…The results of this study were correlated with previous research conducted by Andreas in 2019, where there was no relationship between leukocytes and urine protein in third-trimester pregnant women. 13 This could be due to the failure to divide the severity of COVID-19. Previous studies showed that proteinuria in moderate, severe, and critical COVID-19 was 4.7%, 27.6%, and 63.2%, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Pemeriksaan kimia urine menjadi salah satu pendeteksi dini penyakit pada sistem urinaria yang disebabkan oleh kelainan fungsi ginjal maupun kelainan struktur. Adanya pemeriksaan kimia urine dengan menggunakan bahan urine dilakukan untuk membantu dalam proses pengobatan klinik (Santoso & Laila, 2019).…”
Section: A Pendahuluanunclassified
“…Selain itu,, berbagai asam amino akan masuk sebagai senyawa antara dalam prsoses siklus krebs. Gugus amino dari penguraian asam amino akan di transport ke hati untuk dirubah menjadi ammonia (NH3) dan selanjutnya dibuang melalui urine (Santoso and Laila, 2019). Pada individu yang sehat, pengeluaran protein urine <150 mg setiap harinya.…”
Section: Pendahuluanunclassified
“…Pemeriksaan urine merupakan upaya analisa yang diperlukan untuk mendeteksi penyakit pada system urinarius . Hasil pemeriksaan sampel urine dapat digunakan untuk skrining kesehatan dan penegakan diagnosis dan membantu dalam proses pengobatan klinik (Santoso and Laila, 2019).…”
Section: Pendahuluanunclassified